The Effect of Pollution on Worker Productivity: Evidence from Call-Center Workers in China - Tom Chang; Joshua Graff Zivin; Tal Gross; Matthew Neidell (Institute for the Study of Labor (IZA), 2016)
We investigate the effect of pollution on worker productivity in the service sector by focusing on two call centers in China. Using precise measures of each worker's daily output linked to daily measures of pollution and meteorology, we find that higher levels of air pollution decrease worker productivity by reducing the number of calls that workers complete each day. These results manifest themselves at commonly found levels of pollution in major cities throughout the developing and developed world, suggesting that these types of effects are likely to apply broadly. When decomposing these effects, we find that the decreases in productivity are explained by increases in time spent on breaks rather than the duration of phone calls. To our knowledge, this is the first study to demonstrate that the negative impacts of pollution on productivity extend beyond physically demanding tasks to indoor, white-collar work.
Keywords: J22; J24; Q51; Q53; 330; pollution; productivity